Electronic health record-based identification of inpatients receiving antibiotic treatment for community-acquired pneumonia - David Yang; Leigh Cressman; Keith W. Hamilton; Lauren Dutcher (Cambridge University Press, 2024)
We conducted a retrospective study to assess performance of provider-selected antibiotic indication (PSI) in identifying hospitalized adults with community-acquired pneumonia. PSI showed moderate sensitivity (64.4%) and high specificity (96.3%). PSI has potential utility for targeted real-time antibiotic stewardship interventions, though future research should investigate methods to improve sensitivity.